The ITER Tokamak Exhaust Processing System Permeator and Palladium Membrane Reactor Design. (17th November 2019) - Wilson, Jason; Becnel, James; Demange, David; Rogers, Bernice
Abstract: The tokamak exhaust processing (TEP) system performs chemical separations on ITER fuel cycle process streams. TEP recovers hydrogen isotopes (Q2 ) from impurities such as argon, nitrogen, tritiated water (Q2 O), tritiated ammonia (NQ3 ), and tritiated hydrocarbons such as methane (CQ4 ). TEP sends the hydrogen isotopes for subsequent processing to the isotope separation system or the storage and delivery system. At the same time, an impurity gas stream of extremely low tritium content (less than 8.88 TBq of tritium per day) is produced and sent to the detritiation system (DS). To accomplish the separation, the major hydrogen processing subsystems within TEP are hydrogen-like processing (HLP) and air-like processing/water-like processing (ALP/WLP). (Hydrogen-like gases are Q2, He, and Ne; air-like gases are Ar, O2, N2, O2, and CQ4 ; and water-like gases are Q2 O and NQ3 ). The main processing equipment used for the HLP is a series of palladium-silver permeators (PMs) with ALP/WLP using a series of Palladium Membrane Reactors (PMRs). Aspen Dynamics is the primary tool for verifying system performance of the TEP design. Aspen Dynamics is a commercial, equation-based simulation package for chemical processing. The software enables the user to develop a process model from predefined unit-operation models or construct its own unique unit-operations model. Verification of the TEP simulation model to experimental data was achieved during the TEP conceptual design. The designs for the TEP HLP and ALP/WLP subsystems are examined for the updated gas inputs in terms of compositions and flow rates. The TEP simulation is used to predict tritium output of the TEP processing subsystems This paper describes how the Aspen model of the equipment was improved and used to size the equipment (PMs and PMRs) to process the various gas streams and maintain the discharge to DS to below the limit.